Aedes aegypti vector competence studies: A review - Souza-Neto, Jayme A.; Powell, Jeffrey R.; Bonizzoni, Mariangela (Infection, genetics and evolution, 2019)
Aedes aegypti is the primary transmitter of the four viruses that have had the greatest impact on human health, the viruses causing yellow fever, dengue fever, chikungunya, and Zika fever. Because this mosquito is easy to rear in the laboratory and these viruses grow in laboratory tissue culture cells, many studies have been performed testing the relative competence of different populations of the mosquito to transmit many different strains of viruses. We review here this large literature including studies on the effect of the mosquito microbiota on competence. Because of the heterogeneity of both mosquito populations and virus strains used, as well as methods measuring potential to transmit, it is very difficult to perform detailed meta-analysis of the studies. However, a few conclusions can be drawn: (1) almost no population of Ae. aegypti is 100% naturally refractory to virus infection. Complete susceptibility to infection has been observed for Zika (ZIKV), dengue (DENV) and chikungunya (CHIKV), but not yellow fever viruses (YFV); (2) the dose of virus used is directly correlated to the rate of infection; (3) Brazilian populations of mosquito are particularly susceptible to DENV-2 infections; (4) the Asian lineage of ZIKV is less infective to Ae. aegypti populations from the American continent than is the African ZIKV lineage; (5) virus adaptation to different species of mosquitoes has been demonstrated with CHIKV; (6) co-infection with more than one virus sometimes causes displacement while in other cases has little effect; (7) the microbiota in the mosquito also has important effects on level of susceptibility to arboviral infection; (8) resistance to virus infection due to the microbiota may be direct (e.g., bacteria producing antiviral proteins) or indirect in activating the mosquito host innate immune system; (9) non-pathogenic insect specific viruses (ISVs) are also common in mosquitoes including genome insertions. These too have been shown to have an impact on the susceptibility of mosquitoes to pathogenic viruses. One clear conclusion is that it would be a great advance in this type of research to implement standardized procedures in order to obtain comparable and reproducible results. •Aedes aegypti is easy to rear and manipulate in the laboratory•Variation in vector competence is partly related to the high genetic diversity within and among Ae. aegypti populations•Standardized procedures to assess vector competence would greatly aid in comparable and reproducible findings•Almost no population of Ae. aegypti is 100% naturally refractory to arboviral infection•Virus adaptation to Ae. aegypti mosquitoes is still controversial•Co-infection studies with two or more viruses are still limited•Further investigation is needed to evaluate the role of gut bacterial diversity and the viriome on vector competence